2020
DOI: 10.1152/ajpheart.00749.2019
|View full text |Cite
|
Sign up to set email alerts
|

PKCδ causes sepsis-induced cardiomyopathy by inducing mitochondrial dysfunction

Abstract: Sepsis-induced cardiomyopathy (SIC) is associated with increased patient mortality. At present, there are no specific therapies for SIC. Previous studies have reported increased reactive oxygen species (ROS) and mitochondrial dysfunction during SIC. However, a unifying mechanism remains to be defined. We hypothesized that PKCδ is required for abnormal calcium handling and cardiac mitochondrial dysfunction during sepsis and that genetic deletion of PKCδ would be protective. Polymicrobial sepsis induced by cecal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Mitochondria play a vital role in maintaining the homeostasis of cardiomyocytes, which could be disrupted by excessive ROS. Accumulating evidence demonstrates that septic cardiomyopathy involves mitochondrial dysfunction (Chen et al, 2019;Stanzani et al, 2019;Joseph et al, 2020). Mitochondrial ROS are the driving force of mitochondrial dysfunction in septic cardiomyopathy (Joseph et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria play a vital role in maintaining the homeostasis of cardiomyocytes, which could be disrupted by excessive ROS. Accumulating evidence demonstrates that septic cardiomyopathy involves mitochondrial dysfunction (Chen et al, 2019;Stanzani et al, 2019;Joseph et al, 2020). Mitochondrial ROS are the driving force of mitochondrial dysfunction in septic cardiomyopathy (Joseph et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence demonstrates that septic cardiomyopathy involves mitochondrial dysfunction (Chen et al, 2019;Stanzani et al, 2019;Joseph et al, 2020). Mitochondrial ROS are the driving force of mitochondrial dysfunction in septic cardiomyopathy (Joseph et al, 2020). Studies have found that in septic cardiomyopathy, mitochondrial dysfunction is a key contributor to impaired mitochondrial function and increased mitochondrial fission, leading ultimately to mitochondrial dysfunction and cardiomyocyte apoptosis (Haileselassie et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress has been considered as another player in the progression of septic cardiomyopathy. Previous studies showed that the excessive generation of ROS may cause oxidative stress damage to the mitochondria of cardiomyocytes during septic cardiomyopathy 12,42 . Multiple antioxidant enzymes (eg SOD) are crucial to protect against mitochondrial oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…A cytosolic protein, the inflammatory regulator protein kinase C-delta (PKCδ), is also involved in mediating BBB damage during SAE. PKCδ depletion in isolated cardiomyocytes was found to reduce ROS production and prevent changes in inner mitochondrial membrane potential after LPS treatment (20 ng/mL for 1 h) (25). In rats, CLP-induced PKCδ activation and BBB permeability, as evaluated by Evans Blue extravasation into the brain tissue, were attenuated by the treatment with a PKCδ peptide inhibitor, PKCδ-TAT (48).…”
Section: Brain Endothelial Cellsmentioning
confidence: 91%